2015
DOI: 10.1016/j.firesaf.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Upward flame spread over discrete fuels

Abstract: Upward flame spread over discrete fuels has been analyzed through experimental research on vertical arrays of alternating lengths of PMMA and insulation. By manipulating the lengths of the PMMA fuel and the insulation, several important trends related to flame spread were identified and assessed.The peak flame spread rate for arrays with 4 cm lengths of PMMA occurred at a fuel percentage of 67%; for arrays with 8 cm PMMA, a peak flame spread rate occurred at fuel percentages of 67%, 80%, and 89%. It has been h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…performed experiments on a vertically mounted PMMA slab of identical width; the infrared images showed that the background contribution of the soot was hardly visible, minimally affected the extracted temperatures, and contributed very homogeneously. Miller and Gollner [18] performed several small-scale experiments using thermocouples and an infrared camera simultaneously; the temperature readings of the infrared images were similar to the thermocouple values. The differences between the absolute temperatures from the infrared data and thermocouples were acceptable (the average percentage difference was 3.4%).…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…performed experiments on a vertically mounted PMMA slab of identical width; the infrared images showed that the background contribution of the soot was hardly visible, minimally affected the extracted temperatures, and contributed very homogeneously. Miller and Gollner [18] performed several small-scale experiments using thermocouples and an infrared camera simultaneously; the temperature readings of the infrared images were similar to the thermocouple values. The differences between the absolute temperatures from the infrared data and thermocouples were acceptable (the average percentage difference was 3.4%).…”
Section: Methodsmentioning
confidence: 93%
“…The detector had an uncooled focal plane array micro-bolometer, the spectral band was 7.5 lm to 14 lm, and the emissivity adjustable range was 0.01 to 1.0. With a selection range of spectral response of 8 lm to 12 lm [18,19] in the tests, the infrared thermography filtered the emission bands from those of carbon dioxide, which emits strongly at 2.7 lm and 4.3 lm [19][20][21][22], and water vapor, which emits strongly at 2.7 lm and 6.3 lm [23]. Parent et al [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They developed models to predict horizontal flame spread rate and the number of burning wooden dowels. The vertical flame spread behavior of discrete PMMA was studied by Miller and Gollner [14]. They found that the flame spread rate first increased and then decreased with the increase of PMMA coverage, and reached the maximum as the coverage was 0.67.…”
Section: Introductionmentioning
confidence: 99%